Cross-cultural counselling and psychotherapy to refugees: Psychosocial needs and cultural differences - Γιωτσίδη Βασιλική; Σταλίκας Αναστάσιος (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF